A 14-year nationwide epidemiological analysis of delayed endolymphatic hydrops in Japan. (3rd August 2022) - Ito, Shinsuke; Takakura, Hiromasa; Akaogi, Katsuichi; Shojaku, Hideo; Takeda, Noriaki; Suzuki, Mamoru; Watanabe, Yukio; Aoki, Mitsuhiro; Doi, Katsumi; Ikezono, Tetsuo; Kakigi, Akinobu; Kitahara, Tadashi; et al.
Abstract: Background: Delayed endolymphatic hydrops (DEH) is an inner ear disease that causes recurrent vertigo in the ipsilateral ear or fluctuating hearing in the contralateral ear due to endolymphatic hydrops secondary to preceding deafness. There are few reports of large, multicentre studies investigating the clinical-epidemiological characteristics of DEH. Objective: This study aimed to clarify the characteristics of DEH in Japan. Methods: Clinical data on 662 patients with DEH were analysed by nationwide, multicentre surveys conducted by the Peripheral Vestibular Disorders Research Group of Japan. Results: The proportion of ipsilateral DEH (IDEH) was slightly higher than that of contralateral DEH (CDEH) at 55.4%. The time delay between onset of precedent deafness and onset of DEH was significantly longer for CDEH than for IDEH. The most common cause of precedent deafness was a disease of unknown cause with onset in early childhood (33.1%). Epidemiological characteristics were not significantly different between CDEH with and without vertigo. Conclusion: DEH appearing to be caused by viral labyrinthitis has a high rate of onset within 40 years of precedent deafness. Clinical and epidemiological characteristics of IDEH, CDEH with vertigo, and CDEH without vertigo were very similar. Significance: The clinical-epidemiological characteristics of DEH in Japan were clarified.